KONSEPSI FORCE MAJEURE DALAM KONTRAK/PERJANJIAN DI MASA PANDEMI - Erniwati Erniwati (SOL JUSTICIA, 2020)
Pandemics and policy psbb practical shut down all the achievement by the powerful economic down. From the first can move about , and should be closed. Originally offered, goods and services then got to let business not budged. Phenomenon make the economic potential attenuating, tipped purchasing power, etc. So that, the business world, for him with a pandemic and psbb this, they are in a position that this difficult this, start to make the concept of “force majeure”, as legal terminology had to sit back into public conversation these days. By using the method of juridical normative , writer had some problems related to conception force majeure is fundamental , first , the extent to which it can be said that a situation as in the case of force majeure ? What impact of the state of force majeure on the implementation of the agreement ? As a result , it can be said that this is the kind of force majeure pandemics relatively as in a temporary condition , so when it is back to normal , so entrepreneurs and the committed himself into a contract / agreement , performance can be met back when back to normal.